2000
DOI: 10.1530/eje.0.1420042
|View full text |Cite
|
Sign up to set email alerts
|

A four year dose-response study of recombinant human growth hormone treatment of growth hormone deficient children: effects on growth, bone growth and bone mineralization

Abstract: To evaluate the effects of two regimens of recombinant human GH (rhGH) on growth, bone growth and bone mineralization in GH deficient children, we studied two groups (A and B), each including 16 GH deficient children matched for sex, age, body mass index, height, height velocity and bone age/ chronological age ratio (BA/CA). Group A was treated with a weekly rhGH dose of 1 IU/kg and group B with 0.5 IU/kg. After four years of therapy, we evaluated the auxological outcome, bone morphometry (metacarpal index: MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…Furthermore, local overexpression of IGF-I has been shown to increase trabecular bone formation and osteoblastic cell proliferation in unloaded rats (21). At the higher doses employed in this study, however, GH seems to have mainly a permissive role in mineralization, since in a previous study we could not find any difference in the bone mineral density of the radius and of the metacarpal bone in two groups of GHD children similarly treated (22).…”
Section: Discussioncontrasting
confidence: 40%
“…Furthermore, local overexpression of IGF-I has been shown to increase trabecular bone formation and osteoblastic cell proliferation in unloaded rats (21). At the higher doses employed in this study, however, GH seems to have mainly a permissive role in mineralization, since in a previous study we could not find any difference in the bone mineral density of the radius and of the metacarpal bone in two groups of GHD children similarly treated (22).…”
Section: Discussioncontrasting
confidence: 40%
“…European and Japanese investigators have also observed an increase in height gain in terms of HSDS or height velocity SDS in cohorts of prepubertal children with GHD treated with rhGH for up to 4 years at two different doses (47 and 71 μg/kg/day) [18,19]. A comparative analysis of two large observational registries tracking the efficacy and safety of long-term Norditropin® treatment showed that >75% of prepubertal children with GHD and other short stature indications reached a height within the normal range (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…BA acceleration was also verified by the reduction in CA/BA ratio in all patient groups after the first and second years of treatment. Radetti et al (15) have reported that high dose GH treatment did not significantly advance BA. Frindik et al (16) have proposed that patients with mildly delayed BA before puberty showed faster BA acceleration during puberty with GH treatment compared to those with more severe BA delay.…”
Section: Discussionmentioning
confidence: 97%